Protein adsorption by nanomechanical mass spectrometry: Beyond the real-time molecular weighting - Stachiv, Ivo; Kuo, Chih-Yun; Li, Wei (Frontiers in Molecular Biosciences, 2023)
Knowledge of the dynamics of protein(s) adsorption / interaction with various substrate surfaces together with the label-free detection of protein in a real time are of emergent importance to not only the basic science but also many practical applications such as biocatalysis, fuel cells, biosensors or biomaterials. During past decades an enormous progress in understanding the mechanisms of the intermolecular interactions between protein and surface at the single molecule level has been achieved. This progress which can be linked to the recent advances in nanotechnology and nanomaterials, has enabled to gain insight the functions of many different proteins in even almost their native environment. It is widely accepted by the scientific community that this understanding will possibly help to design a new family of highly sensitive diagnostic tools or novel biomedical devices. Hence, a large number of experimental methods such as atomic force microscopy, optical microscopy, surface plasmon resonance, ellipsometry, Quartz crystal microbalance, standard and nanomechanical mass spectrometry has already been developed to detect and analyze the protein adsorption. Here, we highlight the recent studies focusing on the label-free single molecule detection and studies describing the progress in the modelling of protein adsorption. Nanomechanical techniques are capable to detect and manipulate proteins at even the single-molecule level, therefore they are expected to open a new way of studying dynamics of protein functions. It is noteworthy that all currently developed experimental devices are capable to provide only a limiting number of protein parameters like molecular weight, stiffness or generated surface stress.